2019
DOI: 10.1038/s41419-019-1371-1
|View full text |Cite
|
Sign up to set email alerts
|

CHD1L contributes to cisplatin resistance by upregulating the ABCB1–NF-κB axis in human non-small-cell lung cancer

Abstract: Chromodomain helicase/ATPase DNA binding protein 1-like gene (CHD1L) is a recently identified gene associated with malignant tumor progression and patient chemotherapy resistance in human hepatocellular carcinoma (HCC). Previously, we found an association between CHD1L overexpression and poor patient survival in non-small-cell lung cancer (NSCLC). However, little is known about the relationship between CHD1L expression and chemotherapy resistance of NSCLC. By employing immunohistochemistry, we analyzed the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 35 publications
2
25
0
Order By: Relevance
“…Five of these loci are known to be under recent positive selection, harboring genes involved in immune response (NBPF1 37 , HLA 38 ), nutrition (LCT 39 , LDLR 40 ), and mucus production (MUC2 23 ). We also identified 7 other loci, harboring genes related to immune response (MRC1, playing a role in both the innate and adaptive immune systems 41 , and BCAM, encoding the Lutheran antigen system, also associated with low density lipoprotein cholesterol measurement 42 ), mucus production (CAPN8, involved in gastric mucosal defense 43 ), tumor growth (CHD1L, associated with tumor progression and chemotherapy resistance in human hepatocellular carcinoma 44 , and BANP, encoding a tumor suppressor and cell cycle regulator protein 45 ), as well as genetic disorders (HYDIN, causing primary ciliary dyskinesia 46 , and EFTUD2, causing mandibulofacial dysostosis with microcephaly 47 ). We checked that these regions are not extreme in recombination rate or marker density (Supplementary Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…Five of these loci are known to be under recent positive selection, harboring genes involved in immune response (NBPF1 37 , HLA 38 ), nutrition (LCT 39 , LDLR 40 ), and mucus production (MUC2 23 ). We also identified 7 other loci, harboring genes related to immune response (MRC1, playing a role in both the innate and adaptive immune systems 41 , and BCAM, encoding the Lutheran antigen system, also associated with low density lipoprotein cholesterol measurement 42 ), mucus production (CAPN8, involved in gastric mucosal defense 43 ), tumor growth (CHD1L, associated with tumor progression and chemotherapy resistance in human hepatocellular carcinoma 44 , and BANP, encoding a tumor suppressor and cell cycle regulator protein 45 ), as well as genetic disorders (HYDIN, causing primary ciliary dyskinesia 46 , and EFTUD2, causing mandibulofacial dysostosis with microcephaly 47 ). We checked that these regions are not extreme in recombination rate or marker density (Supplementary Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…5 of these loci are known to be under recent positive selection, harboring genes involved in immune response ( NBPF1 (33), HLA (34)), nutrition ( LCT (35), LDLR (36)) and mucus production ( MUC2 (22)). We also detected 7 novel loci, harboring genes related to immune response ( MRC1 , playing a role in both the innate and adaptive immune systems (37), and BCAM , encoding the Lutheran antigen system, also associated with low density lipoprotein cholesterol measurement (38)), mucus production ( CAPN8 , involved in gastric mucosal defense (39)), tumor growth ( CHD1L , associated with tumor progression and chemotherapy resistance in human hepatocellular carcinoma (40), and BANP , encoding a tumor suppressor and cell cycle regulator protein (41)), as well as genetic disorders ( HYDIN , causing primary ciliary dyskinesia (42), and EFTUD2 , causing mandibulofacial dysostosis with microcephaly (43)). We checked that these regions are not extreme in recombination rate or marker density (Supplementary Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…Yang et al identified ABCB1 as a vital downstream target of the chromosomal helicase/ATPase DNA-binding protein 1-like gene in NSCLC cells. The knockout of ABCB1 and ectopic expression of the chromosomal helicase/ATPase DNA-binding protein 1like gene enhanced the effect of cisplatin on NSCLC cell apoptosis [73]. Regarding LDLR, Yang et al demonstrated that T lymphocytes (LMPs) exert antiangiogenic and proapoptotic effects that lead to inhibition of lung carcinoma by decreasing the vascular endothelial growth factor levels, and the knockdown of LDLR reduces the uptake of LMPs by Lewis lung carcinoma cells and attenuates the inhibitory effects of LMPs on cell growth and vascular endothelial growth factor expression.…”
Section: Discussionmentioning
confidence: 99%